2018
DOI: 10.4172/2161-0401.1000190
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Halogen-Containing Norbornene Adducts Based on N-Substituted Imides of 2,3-Dichlorbicyclo [2.2.1] Hept-5-ene-2,3- Dicarboxylic Acids and Hexachlorocyclopentadiene

Abstract: Diene condensation of N-substituted 2,3-dichlorobicyclo [2.2.1] hept-5-ene-2,3-dicarboxylic acid imides with hexachlorocyclopentadiene proceeds regioselectively through the double bond of dienophile, resulting in the corresponding polychlorinatedcyclic adducts with endo configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The compounds of the bicycle-[2.2.1]hept-and [2.2.2]oct-5-ene series are known to have a wide spectrum of biological and physiological action [4][5][6][7][8][9]12] and, accordingly, our works [4,6,8,10,11,13], devoted to the study of the reaction of diene synthesis of N-aryldichloromaleinimides with cyclopentadiene (CPD), have shown that the obtained compounds are included in the sphere of action of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds of the bicycle-[2.2.1]hept-and [2.2.2]oct-5-ene series are known to have a wide spectrum of biological and physiological action [4][5][6][7][8][9]12] and, accordingly, our works [4,6,8,10,11,13], devoted to the study of the reaction of diene synthesis of N-aryldichloromaleinimides with cyclopentadiene (CPD), have shown that the obtained compounds are included in the sphere of action of these compounds.…”
Section: Introductionmentioning
confidence: 99%